The Influence of Polysaccharides from Sea Algae on the Pathogenetic Targets of Helicobacter Pylori — a New Direction in Therapy and Prevention of Infection - N. N. Besednova; T. A. Kuznetsova; T. S. Zaporozhets; S. P. Kryzhanovsky; A. K. Gazha; E. Yu. Dobryakov; T. N. Zvyagintseva (Антибиотики и Химиотерапия)
According to epidemiological data, 60% of the world's population suffers from Helicobacter pyloriinfection. The multicomponent treatment used in 18–20% of cases does not allow eradication of H.pylori. In addition, reinfection with H.pylori occurs in the majority of treated patients in 3–5 years. An alternative to antibiotics in the treatment of this infection are seaweed products, in particular extracts and polysaccharides with anti-adhesive, anti-toxic, immunomodulatory, antioxidant, and anti-inflammatory properties. Furthermore, algae polysaccharides have direct bactericidal effect and can destroy biofilms formed by H.pylori. The modern materials presented in the literature review indicate the prospects of developments related to the use of extracts and polysaccharides from seaweed as the basis for drugs, dietary supplements and functional food products for the prevention and treatment of H.pylori infection.